STUDY OF BENTHIC DIATOM POPULATIONS IN BUNGKUTOKO WATERS IN RELATION TO THE CONSTRUCTION OF A CONTAINER PORT - Udin S, Riska; Kasim, Ma’ruf; Salwiyah, Salwiyah (Hasanuddin University, 2024)
Diatoms are a unique and specific group of microscopic algae, the body is composed of two valves, namely epitheca and hypotheca to form frustules, with cell walls made of silica (SiO3). Benthic diatom populations are highly variable and are common in waters. Bungkutoko Island is an island located at the eastern end of Kendari Bay. The rapid development and reclamation activities in the Bungkutoko coastal area, especially the construction of the port will affect the structure and topography of the environment. This study aims to determine the population of benthic diatoms in Bungkutoko waters in relation to the construction of a container port. The research was conducted at six observation stations using the purposive sampling method in August-September 2023. The results of this study found 13 genera of benthic diatoms, with abundance values ​​ranging from 342-492 ind/cm2. The diversity index value ranged from 1.82-2.00, the uniformity index value ranged from 0.82-0.91 and the dominance index value range from 0.15-0.20. Principal component analysis showed a correlation between the abundance of benthic diatoms and water quality parameters in the Bungkutoko waters.